Greek Tragedy, European Odyssey : the Politics and Economics of the Eurozone Crisis. - Godby, Robert. (Verlag Barbara Budrich, 2016)
Is the Euro really the crowning achievement of half a century of European integration efforts? Quite the contrary: the Euro has now become a great threat to the European Union as such. Strains caused by the crisis have led to greater dissension among member states and a public recoil against greater integration. This book explains the impact which the ongoing Eurocrisis has already had on the member states and their inhabitants. It does so without assuming that the reader is already an expert on any of the topics addressed, making it a thorough and convenient introduction to the problem.